β-Glucan induced plasma B cells differentiation to enhance antitumor immune responses by Dectin-1 - Yu Bai; Jun Ding; Liuyang He; Zhichao Zhu; Jie Pan; Chunjian Qi (BMC Immunology)
Abstract Background B lymphocytes, essential in cellular immunity as antigen-presenting cells and in humoral immunity as major effector cells, play a crucial role in the antitumor response. Our previous work has shown β-glucan enhanced immunoglobulins (Ig) secretion. But the specific mechanisms of B-cell activation with β-glucan are poorly understood. Here, we took advantage of β-glucan to improve the antitumor immune response of B cells. Results In vitro experiments demonstrate that β-glucan enhance the differentiation of B220lo CD138+ B cells, up-regulate co-stimulatory molecules, and increase the production of cytokines and Ig in response to various antigens. Using the Dectin-1 knockout mice, we revealed that β-glucan modulate B cell immune responses dependent on Dectin-1 receptor. In mouse models of Lewis lung cancer (LLC) tumors, combining β-glucan with programmed death-1(PD-1) blocking antibodies led to increase recruitment of CD19+ B cells in the tumor microenvironment (TME), higher numbers of germinal centers B cells (GC B) in the spleen and draining lymph node (DLN), elevate Ig production, and delay tumor progression. Conclusions These findings reveal that β-glucan can serve as a potent adjuvant to modulate B cell immune responses in a Dectin-1 dependent manner and improve immune checkpoint blockade (ICB) therapy in antitumor. Clinical trial number Not applicable.